(Assessment of Soil Salinity in Kroum-Elkhial Area (west of Tobruk city - Libya - Ahmadoun, Abu Bakr Bakheet Abu Bakr; Abbas, Mohamed Faraj Awad (Journal of natural sciences, life and applied sciences, 2019)
The study was conducted in west side of Tobruk city in area extend from east of Tobruk to Eikrama west، longitude 23°49'35.14"and 23°5.'5.70" east، latitude between 32°.5'55.77 and 32°.5'24.97"north. The total area about 80 hectares، 83m above the sea.Kroum-Elkhial specialized with semi desert climate، change from desert climate by the effects of Mediterranean sea climate in temperature and other climate factors، the rain considered the main source of water (100-170mm/year)، in these area depend on rain water because the high salinity of underground water and not suite of drinking and agriculture activities. The study aimed to evaluate the salinity of the soil and the possibility of expansion in the cultivated area.The study followed the analytical experimental method، the composite samples was collected from the study area as representative samples، randomize Zigzag method was used in sampling، total number of samples was 20 with same size and weight، the depth of sampling is 0-30cm. Soil was represented in basic map، and formed to determinate، PH، EC، TDS، Ww in soil sample، IBM SPSS، Version 21 statistic program was use، and Microsoft Office Excel using to draw distribution the values، to assess the salinity of soil in study area. The results analysis show a medium level of saline، the total percentage of soluble salts in the soil samples ranged from 0.15 to 0.35%. The electrical conductivity in the samples did not exceed 14.6 mmol / cm، according to classification of (FAO).(1977)، the soil in study area suite for (Palm، pomegranate tree، Figs، Olive، Grapes، )as fruits crops، also (Tomatoes، Pepper، Onions، Pumpkin، Cabbage) as a vegetables crops، and(Barley، Wheat، Corn، Sunflower، cotton) as a seeds crops. With attention and government supply، we can increasing and export the production of these crops.
Keywords: moisture content = Ww; electrical conductivity = EC; total dissolved salts = (TDS)